Roles of project steering committees in large agricultural projects in Cameroon (International Journal of Scientific Research and Management (IJSRM), 2023)
Purpose: This study investigated the effective functioning of an agricultural project steering committee, which is considered the driver of a large-scale project given critical roles entrusted to them. Method: A survey of 90 project owners who benefited from two large agricultural projects and members of steering committees was conducted, including semi-structured interviews with five experienced steering committee members. The collected data was analysed using Statistical Package for the Social Sciences version 25, comparing the response of project owners and steering committee members in relation to the function of the steering committee. Results: The result revealed that steering committee members’ top three functions were validation of project results, custodian of project governance and review of project performance. These functions differ from the suggestion from the literature that steering committee members’ top three functions are to identify project priorities, identify and manage potential risks, and provide steering on budget, schedule, and quality. Implication: The work provides expert views on the steering committee in large scale agricultural projects as it clearly shows a misconstruction of their most essential functions, which may be attributed to limited formal communication between the steering committee and project owners and less clarity in their sphere of influence concerning the implementation of large-scale agricultural project. Therefore, roles and responsibilities in relation to functions of the steering committee should be defined at the onset of the project, with a clear indication of their sphere of influence to improve project management and guarantee success.